Opportunities and technical challenges in next-generation sequencing for diagnosis of rare pediatric diseases. (2nd October 2016) - Bacchelli, Chiara; Williams, Hywel J.
ABSTRACT: Introduction : Rare pediatric diseases are clinically severe with high rates of mortality and morbidity. This paper outlines how next-generation sequencing (NGS) can be used to greatly advance identification of the underlying genetic causes. Areas covered : This manuscript is a blend of evidence obtained from literature searches from PubMed and rare disease related websites, laboratory experience and the author's opinions. The paper covers the current state of the field and identifies where the challenges lie and how they are being overcome, using up-to-date references. Expert commentary : The field of NGS is still relatively new but it has already transformed the field of rare disease research. Technological advances in instrumentation, computational hardware and software have resulted in the identification of many causative genes, but as sequencing moves into population-scale initiatives standardisation and data sharing is going to be of paramount importance to ensure we derive the maximum benefit for patients.